Hepcidin-ferroportin axis controls toll-like receptor 4 dependent macrophage inflammatory responses in human atherosclerotic plaques. Issue 2 (August 2015) - Habib, Anwer; Polavarapu, Rohini; Karmali, Vinit; Guo, Liang; Van Dam, Richard; Cheng, Qi; Akahori, Hirokuni; Saeed, Omar; Nakano, Masataka; Pachura, Kimberly; Hong, Charles C.; Shin, Eric; et al.
Abstract: Objectives: Toll-like Receptor 4 (TLR4) is implicated in modulating inflammatory cytokines though its role in atherosclerosis remains uncertain. We have recently described a non-foam cell macrophage phenotype driven by ingestion of hemoglobin:haptoglobin complexes (HH), via the scavenger receptor CD163, characterized by reduced inflammatory cytokine production. In this study, we examined the role of iron metabolism in modulating TLR4 signaling in these cells. Methods and results: Areas in human atherosclerotic plaque with non-foam cell, CD163 positive macrophages demonstrated reduced expression of tumor necrosis factor alpha (TNF-α) and interferon-beta (INF-β) compared to foam cells. Human macrophages differentiated in hemoglobin:haptoglobin (HH) complexes expressed the CD163 positive non-foam cell phenotype and demonstrated significantly less TNF-α and INF-β compared to control macrophages when exposed to oxidized LDL (oxLDL) or lipopolysaccharide (LPS). LPS stimulated expression of TNF-α and INF-β could be restored in HH macrophages by pretreatment with hepcidin, an endogenous suppressor of ferroportin1 (FPN), or by genetic suppression of FPN in macrophages derived from myeloid specific FPN knockout mice. LPS stimulated control macrophages demonstrated increase in TLR4 trafficking to lipid rafts; this response was suppressed in HH macrophages but was restored upon pretreatment with hepcidin. Using a pharmacologic hepcidin suppressor, we observed a decrease in cytokine expression and TLR4-lipid raft trafficking in LPS-stimulated in a murine macrophage model. Conclusion: TLR4 dependent macrophage signaling is controlled via hepcidin-ferroportin1 axis by influencing TLR4-lipid raft interactions. Pharmacologic manipulation of iron metabolism may represent a promising approach to limiting TLR4-mediated inflammatory responses.